Characterization and formation mechanism of pits on diamond {100} face etched by molten potassium nitrite. (February 2018) - Li, Liyang; Chen, Xi; Zhang, Wei; Peng, Kun
Abstract: The morphology of diamond surface etched by molten potassium nitrate was investigated and the formantion mechanism of etched pits was disscussed. The inverted pyramid and square-shaped pits were formed on the {111} face and {100} face of diamond particles, respectively. The size and depth of etching pits on {100} face were apparently smaller than that of {111} face, which suggests {100} face has higher stability due to the role of oxygen functional groups absorb on the structure. At a low etching temperature (600 °C), square-shaped pits were firstly formed on {100} face and then gradually changed into octagon shape with the increasing of etching time. The change of shape can be attributed to the configuration of atomic on {100} face of diamond and the change of oxygen partial in molten salt during the etching process. When etch temperature up to 700 °C, the edges direction of the preferentially formed square shape pit became an angle of 45°with the edges of later formed square shape pit which indicated that partial oxygen pressure can effect stability of diamond surface and etching direction. Graphical abstract: Diamond particles were etched by molten potassium nitrate, and the inverted pyramid and square-shaped pits were formed on the {111} face and {100} face of diamond particles, respectively. No graphitization can be observed for the etched sample. Highlights: Inverted pyramid and square-shaped pits formed on {111} and {100} face of diamond particles, respectively. Square shape pit will change into octagon shape pit with the extension of etch time. Formation mechanism of square shape pit was explained by atomic structure and lattice distortion energy.